Rethinking Global Health: A Binding Convention for R&D for Pharmaceutical Products - Germán Velásquez; Xavier Seuba (South Centre, 2011)
This Research Paper is a contribution to the debate and reform process of the WHO to enable it to respond to the health and health policy challenges of the twenty-first century. More specifically, this paper addresses the issue of the pharmaceutical innovation system within the perspective of access to medicines, exploring possible structural changes in the current system. To do so, it addresses the question of how the constitutional powers of the WHO, often ignored by the Organization itself, can contribute positively to a paradigm shift in biomedical research stimulation.
Keywords: 300